Evaluasi Program Trias UKS: Analisis Komprehensif terhadap Pendidikan Kesehatan, Pelayanan Kesehatan, dan Pengelolaan Lingkungan di SMA Sultan Agung 3 Semarang - Pradana P.H, Firmansyah Kholiq; Iqbal, Muhammad (Jurnal Kesehatan, 2024)
The Trias School Health Efforts (UKS), which include health education, health services, and the development of a healthy environment, are strategic efforts to improve the health status of students. This study aims to evaluate the implementation of the Trias UKS program at SMA Sultan Agung 3 Semarang. The research method used is a descriptive survey with a cross-sectional approach, involving 150 respondents consisting of students, teachers, and school health workers. Data were collected through structured questionnaires and field observations, and then analyzed both quantitatively and qualitatively. The results of the study indicate that the implementation of health education falls into the good category, although there are challenges in the provision of health services, particularly regarding the availability of facilities and infrastructure. The development of a healthy environment has been implemented quite effectively but requires increased participation from all school members. Overall, the Trias UKS program at SMA Sultan Agung 3 Semarang has been well-executed, though improvements are needed in certain aspects to achieve more optimal results. This study provides recommendations for policy improvement and program implementation in the school health environment.